Sex-linked Single Nucleotide Polymorphism (SNP) identification and molecular marker development of salacca (Salacca zalacca (Gaertn.) Voss) - RIRY PRIHATINI; DINY DINARTI; AGUS SUTANTO; SUDARSONO SUDARSONO (Society for Indonesian Biodiversity, 2023)
Abstract. Prihatini R, Dinarti D, Sutanto A, Sudarsono. 2023. Sex-linked Single Nucleotide Polymorphism (SNP) identification and molecular marker development of salacca (Salacca zalacca (Gaertn.) Voss). Biodiversitas 24: 704-712. Salacca zalacca (Gaertn.) Voss is a native tropical fruit species of Indonesia with three different sex types, i.e., female, male, and hermaphrodite. Early sex identification plays a vital role in the dioecious plant development, cultivation, and breeding program. The morphological and histological markers cannot differentiate salacca sex types during vegetative stages, during which molecular approaches are offered. Isolation of salacca's partial Transducin Beta Like-3 (TBL3) gene was done using Phoenix dactylifera L. TBL3-specific primers. After DNA sequencing and multiple sequence alignment, the putative TBL3 aligned data was used to construct a phylogenetic tree, find SNAP primers, and use the generated markers as predictors for sex-type phenotypes of salacca. Phylogenetic analysis showed that the dendrogram of aligned TBL3 partial sequences of salacca and other taxa showed that the salacca TBL3 is closely related to P. dactylifera and Elaeis guineensis Jacq. since the three palms belong to the same Arecaceae family. The partial sequence of the TBL3 gene of hermaphrodite salacca revealed ten single nucleotide polymorphisms (SNPs) compared to those of female and male plants. Protein alignment of the sequence also showed several differences, which may lead to different flower morphogenesis. The salacca SNAP sex-types markers were developed from one of the SNP sites and validated using samples from farmer plantations. The SNAP primer pairs of STBL1F-Ref - STBL1-Rev amplified a 300 bp fragment from hermaphrodite samples, whereas no band was amplified from the female and male samples. On the contrary, primers STBL1F-Alt - STBL1-Rev amplified a 300 bp fragment from female and male plants but not from the hermaphrodite plants. The salacca's TBL3 sequences and the SNAP markers are valuable tools for further salacca genomic exploration.